MORPHOMETRY OF FEMALE AND ASSOCIATED MALE STINGLESS BEES OF THE GENUS TETRAGONULA (HYMENOPTERA: APIDAE: MELIPONINI) FROM INDIA - SHASHIDHAR VIRAKTAMATH,; ANUJA NAIK AND D.SHISHIRA, (The Bioscan, 2021)
As a first step to understand the extent of diversity of Indian stingless bees of the genus Tetragonula, morphometry of 346 female and 222 associated male stingless bees from 17 states and Andaman Islands was studied for the first time in India by selecting 36 morphological parameters for female and 30 for male bees. Female and male bees from Meghalaya were the biggest measuring 4.86 and 5.20 mm in length, respectively while female bees from Andhra Pradesh and male bees from Kerala were the smallest with body length of 3.39 and 3.43 mm, respectively. Female bees from Andaman Islands had the widest head measuring 1.88 mm while in males widest head was observed in the bees from Meghalaya. In both female and male bees longest forewings (4.74 and 4.70 mm, respectively) and hind basitarsus (0.74 and 0.63 mm, respectively) was recorded in the bees from Meghalaya. Results of Principal Component analysis resulted in 6 clusters while 8 clusters were formed in Canonical Discriminant analysis of female bees. However, male bees did not form any distinct cluster in Principal Component analysis but in Canonical Discriminant analysis 9 clusters were formed. Both males and female bees from Andaman Islands, Assam, Manipur, Meghalaya, Nagaland and Tripura formed separate individual clusters. Clustering pattern of bees from other states varied. We conclude that Indian fauna of stingless bees belonging to the genus Tetragonula is rich with many unknown species. Further critical studies are needed to identify the species based on male genitalial structures and DNA sequences.